The Role of Religiosity in Explaining the Intention to use Islamic FinTech Among MSME Actors - Rifaldi Majid (Universitas Muhammadiyah Yogyakarta, 2021)
Islamic FinTech is growing rapidly and has become a new alternative of financing for micro, small, and medium enterprises (MSME) which are the backbone of the national economy. This study aims to examine the role of religiosity level of MSMEs actors on the intention to use Islamic FinTech. This research employed Partial Least Square - Structural Equation Modeling (PLS-SEM) method. The data collected using an online questionnaire adapted from previous research, then distributed to 100 Indonesian MSME actors and analyzed using smart PLS. The main result indicated religiosity plays a positively significant role in explaining the intention to use Islamic FinTech. In addition, Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Subjective Norm (SN) were also found to be influential, while both, Attitude Toward Behavior (ATB) and Perceived Behavioral Control (PBC), have no significant effect on behavioral intention. This research implicates the need for collaboration between the Financial Services Authority (OJK) as the regulator with Islamic FinTech institutions to improve literacy, providing incentives, strengthening consumer data protection, as well as integrating the values from the religious anglein the concept and practice of FinTech product and services that are based on Islamic guideline in order to attract the users from MSME actors.